The surface proteins InlA and InlB are interdependently required for polar basolateral invasion by Listeria monocytogenes in a human model of the blood–cerebrospinal fluid barrier - Gründler, Tim; Quednau, Natascha; Stump, Carolin; Orian-Rousseau, Véronique; Ishikawa, Hiroshi; Wolburg, Hartwig; Schroten, Horst; Tenenbaum, Tobias; Schwerk, Christian (Microbes and infection, 2013)
The Gram-positive bacterium Listeria monocytogenes can enter the human central nervous system and cause life-threatening meningitis. During this process the pathogen has to invade and cross diverse cellular barriers involving the functions of the surface proteins Internalin (InlA) and InlB. Whereas the internalin-dependent crossing of the intestinal epithelium and the fetoplacental barrier have been subject to intensive investigation, limited research elucidating the crossing of the human blood–cerebrospinal fluid barrier (BCSFB) has been reported. We have recently established a functional in vitro model of the BCSFB based on human choroid plexus papilloma (HIBCPP) cells. We show polarized expression of receptors involved in listerial invasion (i.e. E-Cadherin, Met) in HIBCPP cells. Infecting HIBCPP cells with the L. monocytogenes strain EGD, we demonstrate polar invasion exclusively from the in vivo relevant basolateral cell side. Intracellular listeria were found in vacuoles and the cytoplasm, where they were often associated with “actin tail”-like structures. Furthermore, the L. monocytogenes wild type strain shows significantly higher internalization rates than isogenic mutants lacking either InlA, InlB or both surface proteins. Deletion of either one or both proteins leads to a similarly decreased invasion, suggesting an interdependent function of InlA and InlB during invasion of choroid plexus epithelial cells.